Macrophage MST1 protects against schistosomiasis-induced liver fibrosis by promoting the PPARγ-CD36 pathway and suppressing NF-κB signaling. - Jianyang Li; Xinyuan Cai; Yan Yang; Yulin Mao; Lin Ding; Qian Xue; Xunhao Hu; Yan Huang; Cong Sui; Yuxia Zhang (PLoS Pathogens)
Schistosomiasis is characterized by egg-induced hepatic granulomas and subsequent fibrosis. Monocyte-derived macrophages play critical and plastic roles in the progression and regression of liver fibrosis, adopting different polarization phenotypes. Mammalian STE20-like protein kinase 1 (MST1), a serine/threonine kinase, has been established to act as a negative regulator of macrophage-associated inflammation. However, the specific role of MST1 in Schistosoma-induced liver fibrosis has not been fully understood. In this study, we demonstrate that macrophage MST1 functions as an inhibitor of inflammation and fibrosis following infection with Schistosoma japonicum (S. japonicum). Mice with macrophages-specific Mst1 knockout (termed Mst1△M/△M) mice developed exacerbated liver pathology, characterized by larger egg-induced granulomas, and increased fibrosis post infection. This was accompanied by enhanced production of proinflammatory cytokines (IL1B, IL6, IL23, TNFA and TGFB) and a shift in macrophage phenotype towards Ly6Chigh. Mechanistically, MST1 activation by soluble egg antigen (SEA) promoted PPARγ-mediated CD36 expression, enhancing phagocytosis and consequently upregulation of fibrolytic genes such as Arg1 and Mmps. Conversely, MST1 deletion leads to up-regulation of pro-inflammatory genes instead of fibrolytic genes in macrophages, accompanied by decreased expression of CD36 and impaired phagocytosis. Furthermore, the ablation of MST1 enhances NF-κB activation in S. japonicum-infected and SEA-stimulated macrophages, resulting in increased production of proinflammatory cytokines. Overall, our data identified MST1 as a novel regulator for egg-induced liver fibrosis via modulation of macrophage function and phenotype by CD36-mediated phagocytosis and suppression of NF-κB pathway.